2014
DOI: 10.7314/apjcp.2014.15.22.9801
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rate of Colorectal Adenoma or Cancer in Unselected Colonoscopy Patients: Indonesian Experience in a Private Hospital

Abstract: Background: Colorectal cancer is currently the third most common cancer in Indonesia, yet colonoscopy -the most accepted mode of screening to date -is not done routinely and national data are still lacking. Objective: To determine the detection rate of colorectal cancers and adenomas in unselected patients undergoing colonoscopy for various large bowel symptoms at the Digestive Disease and GI Oncology Centre, Medistra Hospital in Jakarta, Indonesia. Materials and Methods: Colonoscopy data from January 2009 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Obesity is also considered as an independent risk factor for CRC development [16]. Our large prospective study has shown the significant association between high BMI and presence of NAFLD [11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Obesity is also considered as an independent risk factor for CRC development [16]. Our large prospective study has shown the significant association between high BMI and presence of NAFLD [11].…”
Section: Discussionmentioning
confidence: 85%
“…Several risk factors were confirmed as independent risk factors for NAFLD, that is, obesity, male gender, age of more than 35 years, high triglyceride, low high-density lipoprotein (HDL) cholesterol, and high serum alanine aminotransferase levels [10]. Notwithstanding, retrospective data analysis study of a large sample size in the same private hospital for colon polyps or cancer detection rate found almost similar important risk factors, that is, older age (≥50 years old) and male gender [11].…”
Section: Introductionmentioning
confidence: 93%
“…Hal ini sesuai dengan penelitian yang dilakukan oleh Khan dkk pada tahun 1998. 9,10,11 Hasil penelitian juga sejalan dengan penelitian di Turki dengan 3514 sampel, 470 (13,3%) dimana sampel terbanyak dilakukan polipektomi didapatkan pada laki-laki (61,7%) dengan 66,4% sampel berusia diatas 50 tahun. 12 Pada kelompok polip adenoma, penderita polip diatas usia 50 tahun adalah 71,8% dan yang menderita polip adenoma sebanyak 63,9%.…”
Section: Pembahasanunclassified
“…2 Angka mortalitas KKR di Indonesia 18.958 pasien pada tahun 2012, insiden dan mortalitas yang tinggi ini dikarenakan kurangnya deteksi dini dan kesadaran masyarakat terhadap KKR. 3 Dalam 10 tahun terakhir mortality rate KKR telah menurun lebih dari 20% karena meningkatnya perkembangan teknik diagnostik dan optimasi teknik bedah, terapi neoadjuvant dan paliatif. 4 Modalitas pencitraan yang digunakan dalam tatalaksana KKR saat ini sangat bervariasi dan heterogen di berbagai negara maupun institusi kesehatan.…”
Section: Pendahuluanunclassified